THE ROLE OF POPULISM IN SHAPING POLITICAL DISCOURSE AND POLICY (International Journal of Food and Nutritional Sciences, 2021)
Populism has emerged as a transformative force in contemporary politics, reshaping political discourse and policy-making across the globe. This study examines the multifaceted role of populism, characterized by its appeal to "the people" against a perceived corrupt elite. Populism simplifies complex issues into binary choices, enhancing its appeal and accessibility but often at the expense of nuanced debate. It leverages direct communication channels, such as social media and public rallies, to bypass traditional media and establish a personal connection with supporters, which can intensify political polarization and societal division. In policy-making, populism prioritizes immediate, popular demands, leading to policies that may address short-term grievances but lack long-term viability. It often challenges established democratic norms and institutions, undermining checks and balances and contributing to potential instability. Populist leaders frequently advocate for sweeping reforms and interventions that resonate with their base, which can lead to significant shifts in economic and social policies. The impact of populism is evident in various global contexts, from the rise of populist leaders in the United States and Brazil to the growing influence of populist parties in Europe. These examples illustrate how populism shapes political agendas, alters governance practices, and affects societal cohesion. Understanding the role of populism is crucial for analyzing current political dynamics and addressing the challenges and opportunities it presents in modern governance.